The ARTFIBio web platform. (2015) - Mouriño, J. Carlos; Gómez, Andrés; Sánchez, Mariano; López-Medina, A.
In the last years, there were big steps in the treatment of head and neck cancer (HNC), but local relapse rates are still very high. For this reason, multicentric research is needed to overcome them, focused on quantifying tumour response of HNC patients by functional images like PET/CT and MRI. The joint use of MRI and PET/CT can be useful for delimiting the hypoxic areas. To leverage the collaboration among hospitals and researchers, a platform architecture specifically designed to suit the needs of the study of tumour response quantification is being developed. It allows the sharing of the patient's images, the radiotherapy treatment planning, and the information of the final delivered doses. Other additional information can be added for each patient, as chemotherapy treatment data or the surgical procedures, so a full set of information can be gathered for each treatment. Additionally, the platform includes a registration tool to analyse correctly the different patient's images. Our tool is being successfully used in the frame of the ARTFIBio project, focused on the study of predictive individualised models of head and neck tumour response to radiotherapy.